Mental Health Symptoms and Work-Related Stressors in Hospital Midwives and NICU Nurses: A Mixed Methods Study - Favrod, Céline; Jan du Chêne, Lauranne; Martin Soelch, Chantal; Garthus-Niegel, Susan; Tolsa, Jean-Francois; Legault, Francois; Briet, Virginie; Horsch, Antje (Frontiers in Psychiatry, 2018)
Hospital midwives and neonatal intensive care (NICU) nurses frequently encounter work-related stressors and are therefore vulnerable to developing mental health problems, such as secondary traumatic stress, burnout, anxiety, and depression. However, so far, the exact nature of these work-related stressors (traumatic vs non-traumatic stressors) has not been investigated. This concurrent triangulation mixed methods cross-sectional study aimed to compare mental health symptoms in hospital midwives and NICU nurses, and to identify and compare work-related traumatic and non-traumatic stressors for both professional groups. 122 midwives and 91 NICU nurses of two Swiss university hospitals completed quantitative measures (Secondary Traumatic Stress Scale, STSS; Hospital Anxiety and Depression Scale, HADS; Maslach Burnout Inventory, MBI) and one qualitative question in an online survey. When controlling for socio-demographic variables, NICU nurses had a higher STSS total score and higher STSS subscales scores and less HADS anxiety subscale scores than hospital midwives.Work-related stressors were classified into five themes: “Working environment”, “Nursing/midwifery care”, “Dealing with death and dying”, “Case management” and “Others”. Forty-six (46.3%) percent of these were classified as traumatic work-related stressors. NICU nurses reported more traumatic stressors in their working environment but no other differences between professional groups regarding the total number of work-related traumatic vs. non-traumatic stressors were found. Measures, such as teaching strategies to amend the subjective appraisal of the traumatic stressors or providing time to recover in-between frequently occurring work-related traumatic stressors might not only improve the mental health of professionals but also decrease sick leave and improve the quality of patient care.